ANALYSIS WACANA KRITIS SURAT ELEKTRONIK PRITA MULYASARI - Bayu Aryanto (Dinamika Bahasa dan Budaya, 2009)
A text is always subjectively inferred. The subjectivity may cause polemic among readers of a given text. This also applies to Prita Mulyasari’s electronic reader’s letter on the internet. She was accused of defaming Rumah Sakit Omni International. This article attempts to analyze the said letter in a critical discourse analysis. The rhetorical patterns, speech acts including their moods and principles of politeness were used as the writer’s basis for critically analyzing the text. Key Words: Rhetorical patterns, moods, speech acts, principles of politeness